THE EFFECT OF SUPERVISION AND WORKLOAD ON EMPLOYEE PERFORMANCE IN THE GOVERNMENT OF SOUTH SIBOLGA DISTRICT, SIBOLGA CITY - Vivi Wiyannur Tanjung; Mansur Tanjung; Sinta Veronika Hutabarat (Patua : Journal of Business Administration and Management, 2025)
This study aims to find out whether there is an Influence of Supervision and Workload on Employee Performance in the South Sibolga District Government, Sibolga City. The type of research used in this study is a quantitative research method with a descriptive approach. The population in this study is employees at the South Sibolga Sub-district Office, Sibolga City. The sample is the entire population in the South Sibolga District Government with a questionnaire distribution of 64 respondents. The results of the study found that the correlation coefficient obtained from the result that there was a moderate relationship between Supervision and Employee Performance of 0.550 and the relationship between Workload and Employee Performance of 0.646. Based on the analysis of the Coefficient of Determination obtained of 0.491, this means that what happens in the variation of variables bound to Employee Performance 49.1% is determined by the independent variables of Supervision and Workload simultaneously and the remaining 50.9% is determined by other factors that are not discussed in this study. From the results of the t-test in the study, it is known that the t-value of Supervision (X1) is 2.950 > t table 1.66980 and Workload (X2) is 4.750 > t table 1.66980, so the hypothesis states that Supervision and Workload partially or individually have a significant effect on Employee Performance in the Government of South Sibolga District, Sibolga City, proven and acceptable acceptable. Meanwhile, from the results of the F test, it is known that the F value is calculated as 29.363 > F table 3.15 and the significance is 0.000 < 0.05 so that the hypothesis that Supervision and Workload have a significant effect together or simultaneously on the Performance of Employees in the South Sibolga District Government, Sibolga City, is proven and acceptable to be accepted.